2011
DOI: 10.1021/nl103702j
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Titanium Dioxide Nanorods in 3D-Confined Spaces

Abstract: Three-dimensional (3D) nanowire (NW) networks are promising architectures for effectively translating the extraordinary properties of one-dimensional objects into a 3D space. However, to uniformly grow NWs in a 3D confined space is a serious challenge due to the coupling between crystal growth and precursor concentration that is often dictated by the mass flow characteristic of vapor or liquid phase reactants within the high-aspect ratio submicrometer channels in current strategies. We report a pulsed chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
90
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 52 publications
3
90
2
Order By: Relevance
“…Several approaches to control the size, shape and agglomeration state of TiO 2 nanoparticles have been attempted [4]. Nanotubes [30], nanorods [31,32], monolithic porous structures [15,33,34], inverse opals [35] and microspheres [19,[36][37][38][39][40][41] have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches to control the size, shape and agglomeration state of TiO 2 nanoparticles have been attempted [4]. Nanotubes [30], nanorods [31,32], monolithic porous structures [15,33,34], inverse opals [35] and microspheres [19,[36][37][38][39][40][41] have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) nano-structures such as nanotubes, 1 nanowires, 2 nanowhiskers, 3 nanorods, 4 nanobelts, 5 and nanofibers 6 have been recently studied by many researchers because of its wide range of applications in gas sensors, 7 photocatalysis, 8,9 dye-sensitization for solar cells, 10,11 and solar water splitting for hydrogen production.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to 1D ZnO and SnO2 nanostructures, the growth of high-quality 1D TiO2 nanostructures via the vapour deposition method is much more difficult, due to the existence of multiple polymorphs and the thermodynamically unfavourable crystallography for anisotropic crystal growth, particularly with large aspect ratio [99]. Even though TiO2 nanowires with morphology as perfect as those of ZnO and SnO2 are difficult to achieve, we still can find some attempts to achieve the vapour growth of TiO2 nanostructures [99][100][101][102].…”
Section: Vapour Deposition Growth Of 1d Nanostructuresmentioning
confidence: 99%
“…Even though TiO2 nanowires with morphology as perfect as those of ZnO and SnO2 are difficult to achieve, we still can find some attempts to achieve the vapour growth of TiO2 nanostructures [99][100][101][102]. Shi et al [100] reported the growth of rutile TiO2 nanowires by the pulsed CVD technique from Au seeded substrates at 650°C using TiCl4 and H2O as the precursors.…”
Section: Vapour Deposition Growth Of 1d Nanostructuresmentioning
confidence: 99%